Innovation in Digitalization of UI/UX Design with User Centered Design to Increase Customer Satisfaction - Felicia, Yohana; Ibrahim, Ali; Indah, Dwi Rosa; Seprina, Iin (Politeknik Negeri Batam, 2024)
In the era of rapid digitalization, the economic sector, especially small and medium enterprises, is required to adapt to the development of digitalization. SDS YPMM Cooperative is one example of a small business that still relies on traditional systems in its business processes. To overcome this problem, a website-based User Interface (UI) and User Experience (UX) design was carried out to digitize the SDS YPMM cooperative business process. In the design, the User Centered Design method is used which focuses on user needs. This method is done by Specify the context of use, specify user and organizational requirements, produce design solutions, and evaluate design against user requirements. At the evaluation stage, the System Usability Scale (SUS) was used to measure the level of usability of the resulting design. The evaluation results obtained 179 respondents out of 533 population for the user interface showed a score of 84.97, which falls into the